COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF RELAXATION TECHNIQUES AND PHYSICAL EXERCISE ON CONTROLLED BLOOD PRESSURE: A META-ANALYSIS - Wahidin ‎; Dina Raidanti; Christin Jayanti; Didin Syaefudin; Rina Wijayanti (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Background: Hypertension is a major global public health problem, with prevalence increasing, particularly among adults and older adults. Non-pharmacological interventions such as relaxation techniques and physical exercise are widely recommended for blood pressure control. However, evidence directly comparing the relative effectiveness of these two approaches remains limited and inconsistent. Objective: This study aimed to compare the efficacy of relaxation techniques and physical exercise in reducing blood pressure using a meta-analytic approach. Methods: This meta-analysis was conducted in accordance with PRISMA 2020 guidelines. Randomized controlled trials and quasi-experimental studies evaluating relaxation techniques or physical exercise interventions on blood pressure outcomes were included. Statistical analyses were performed using a random-effects model with standardized mean difference (SMD) as the effect size metric. Heterogeneity and subgroup analyses by age group and intervention type were conducted. Results: A total of 33 studies were included in the analysis. Overall, non-pharmacological interventions significantly reduced blood pressure (SMD = −0.744; p < 0.001). Subgroup analysis showed that relaxation techniques produced a greater reduction in blood pressure (SMD = −0.954) than physical exercise (SMD = −0.570). The largest effect size was observed among older adults (SMD = −1.075). Substantial heterogeneity was identified across studies (I² = 74.1%). Conclusion: Both relaxation techniques and physical exercise are effective non-pharmacological interventions for reducing blood pressure, with relaxation techniques demonstrating greater and more consistent effects, particularly among older adults. These findings provide robust comparative evidence to support evidence-based hypertension management strategies.